Safety of Percutaneous Endoscopic Gastrostomy Placement in Pregnancy: A Case Report and Literature Review - Celine Aslinia; Armand Edalati; Arianna Fallahian; Arya Edalati; Maha Hosseini (Case Reports in Gastrointestinal Medicine)
Gastrostomy tube placement in pregnancy is historically contraindicated due to risk of injury to the developing fetus and exposure to anesthetic agents. However, in cases where oral nutritional access is severely jeopardized, percutaneous endoscopic gastrostomy (PEG) tube placement can be a life-saving measure. In this case report and literature review, we present a case of successful PEG placement in a pregnant woman, followed by a discussion of the existing literature regarding PEG placement during pregnancy.